Radiographic Reread Protocols to Identify Clinically Relevant Errors in Initial Trauma Evaluations. Issue 6 (June 2022) - Morgan, Madison E.; Brown, Catherine T.; Vernon, Tawnya M.; Gross, Brian W.; Wu, Daniel; Bradburn, Eric H.; Werley, Mark; Rogers, Frederick B.
Introduction: Diagnostic radiology interpretive errors in trauma patients can lead to missed diagnoses, compromising patient care. Due to this, our level II trauma center implemented a reread protocol of all radiographic imaging within 24 hours on our highest trauma activation level (Code T). We sought to determine the efficacy of this reread protocol in identifying missed diagnoses in Code T patients. We hypothesized that a few, but clinically relevant errors, would be identified upon reread. Methods: All radiographic study findings (initial read and reread) performed for Code T admissions from July 2015 to May 2016 were queried. The reviewed radiological imaging was given one of four designations: agree with interpretation, minor (non-life threatening) nonclinically relevant error(s)—addendum/correction required or clinically relevant error(s) (major [life threatening] and minor)—addendum/correction required, and trauma surgeon notified. The results were compiled, and the number of each type of error was calculated. Results: Of the 752 radiological imaging studies reviewed on the 121 Code T patients during this period, 3 (0.40%) contained minor clinically relevant errors, 11 (1.46%) contained errors that were not clinically relevant, and 738 (98.1%) agreed with the original interpretation. The three clinically relevant errors included a right mandibular fracture found on X-ray and a temporal bone fracture that crossed the clivus and bilateral rib fractures found on computerized tomography. Discussion: Clinically relevant errors, although minimal, were discovered during rereads for Code T patients. Although the clinical errors were significant, none affected patient outcomes. We propose that the implementation of reread protocols should be based upon institution-specific practices.